Reconstruction of Past Disasters Mitigation in Sěrat Primbon Palintangan Palinḍon Pakědutan (Add.12311): Collective Memory Studies on Maurice Halbwachs’ Perspective - Isna Ilham Nur Rizki; Yosi Wulandari; Ghis Nggar Dwiadmojo; I Kadek Purnawan (JENTERA: Jurnal Kajian Sastra, 2026)
This study aims to examine the Sĕrat Primbon Palintangan Palinḍon Pakĕdutan (Add.12311) as a form of the Javanese people’s collective memory of disasters and reconstruct the culture-based disaster mitigation potential contained within it. This study employs a descriptive qualitative method using Maurice Halbwachs’ collective memory approach. The primary data source is the manuscript Sĕrat Primbon Palintangan Palinḍon Pakĕdutan (Add.12311) from the British Library collection, analyzed through literature review and qualitative content analysis. The results indicate that earthquakes in the Palindon text are understood not only as natural phenomena but also as indicators of social, health, economic, and environmental changes. Experiences regarding social conflict, food crises, disease outbreaks, population displacement, and ecological vulnerabilities are organized as collective memory passed down through Javanese written traditions. This study also found the existence of culture-based disaster mitigation awareness, manifested in vigilance toward environmental changes, the strengthening of social solidarity, preparedness for food and health crises, and the maintenance of socio-ecological balance in the face of crisis situations. Thus, the Palindon texts serve as a medium for transmitting traditional disaster knowledge that remains relevant for strengthening culture-based disaster mitigation in contemporary society. Abstrak Penelitian ini bertujuan untuk mengkaji Sĕrat Primbon Palintangan Palinḍon Pakĕdutan (Add.12311) sebagai bentuk memori kolektif masyarakat Jawa tentang bencana dan merekonstruksi potensi mitigasi bencana berbasis budaya yang terkandung di dalamnya. Penelitian ini menggunakan metode kualitatif deskriptif dengan pendekatan memori kolektif Maurice Halbwachs. Sumber data utama adalah manuskrip Sĕrat Primbon Palintangan Palinḍon Pakĕdutan (Add.12311) dari koleksi British Library, yang dianalisis melalui tinjauan pustaka dan analisis isi kualitatif. Hasil penelitian menunjukkan bahwa gempa bumi dalam teks Palindon dipahami tidak hanya sebagai fenomena alam tetapi juga sebagai indikator perubahan sosial, kesehatan, ekonomi, dan lingkungan. Pengalaman mengenai konflik sosial, krisis pangan, wabah penyakit, pengungsian penduduk, dan kerentanan ekologis diorganisasikan sebagai memori kolektif yang diturunkan melalui tradisi tulis Jawa. Studi ini juga menemukan adanya kesadaran mitigasi bencana berbasis budaya, yang termanifestasi dalam kewaspadaan terhadap perubahan lingkungan, penguatan solidaritas sosial, kesiapan menghadapi krisis pangan dan kesehatan, serta pemeliharaan keseimbangan sosial-ekologis dalam menghadapi situasi krisis. Dengan demikian, teks-teks Palindon berfungsi sebagai media untuk menyampaikan pengetahuan tradisional tentang bencana yang tetap relevan untuk memperkuat mitigasi bencana berbasis budaya dalam masyarakat kontemporer.